A Foreign Body as a Gynaecological and Sexological Issue—Case Study and Literature Review - Aleksander Frąckowiak; Stefan Sajdak; Grażyna Jarząbek-Bielecka; Klaudia Dolińska-Kaczmarek; Katarzyna Plagens-Rotman; Piotr Merks; Tomasz Kościński; Monika Englert-Golon (Medicina)
Introduction: The most commonly encountered foreign body in the vagina is a tampon, which is routinely removed during gynaecological examinations. While these cases are common and well-known in medical practice, there are also situations involving much more unusual foreign bodies. This article focuses on these rare and often surprising cases, which can pose diagnostic and therapeutic challenges. Highlighting this topic aims to draw attention to the variety of situations gynaecologists may encounter in their daily professional practice. Case Study: A 62-year-old woman was admitted to the Gynaecological Obstetric Clinical Hospital of the Poznan University of Sciences to have a foreign body removed from her vagina. An MRI examination revealed a calcified well-defined structure (94 mm × 68 mm × 96 mm). The material removed during surgery were calcified fragments surrounding a plastic deodorant cap. After decalcification of the lesion, a histopathological examination ruled out cancerous cells. The patient received gynaecological and urological treatments due to a vesicovaginal fistula. Conclusions: The gynaecologists’ expertise and skills in diagnosing and removing foreign bodies are essential in order to provide postmenopausal women with comprehensive and responsible medical care.